Burnout Syndrome in medical internship students and its prevention with Balint Group - Calcides,Dâmaris Alejandra Paula (2019)
SUMMARY BACKGROUND: We intend to estimate the Burnout Syndrome prevalence and its associated factors among medical internship students at a public university in northeastern Brasil, besides investigating the Balint Group (BG) contribution in its prevention. METHODS: We conducted a cross-sectional study in February/2018 with Medical Internship Students at the University researched. We applied a structured questionnaire developed by the authors about socio-demographic data, educational process with BG participation, and current psycho-emotional experiences, in addition to the Maslach Burnout Inventory – Student Survey (MBI-SS), for Burnout Syndrome screening. We performed descriptive data analysis, logistic regression, and cluster analysis. RESULTS: A total of 184 students (98%) participated in the study, with a mean age of 25.9±3.9 years, of which 54.9% were men. The prevalence of Burnout Syndrome was 10.3% based on the three-dimensional criterion and 35.9% on two-dimensional criterion (Exhaustion and Cynicism); it was higher in those who thought about quitting the program (OR=2.14), were dissatisfied with the teaching strategies (OR=2.67) and their performance (OR=2.64) and made use of licit drugs (OR=2.37). The variables associated with Burnout Syndrome allowed individuals to be discriminated, classifying them into three subgroups. Burnout Syndrome prevalence decreased, and vulnerability factors were attenuated when there was a higher frequency of students participating in BG. CONCLUSIONS: The prevalence of two-dimensional Burnout Syndrome was high, with factors associated with the educational process. Participation in BG was associated with a lower Burnout rate prevalence. Longitudinal studies should be conducted.